Prediction of Human Papillomavirus Status and Overall Survival in Patients with Untreated Oropharyngeal Squamous Cell Carcinoma: Development and Validation of CT-Based Radiomics - Choi, Y.; Nam, Y.; Jang, J.; Shin, N.-Y.; Ahn, K.-J.; Kim, B.-S.; Lee, Y.-S.; Kim, M.-S. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Human papillomavirus is a prognostic marker for oropharyngeal squamous cell carcinoma. We aimed to determine the value of CT-based radiomics for predicting the human papillomavirus status and overall survival in patients with oropharyngeal squamous cell carcinoma.MATERIALS AND METHODS: Eighty-six patients with oropharyngeal squamous cell carcinoma were retrospectively collected and grouped into training (n = 61) and test (n = 25) sets. For human papillomavirus status and overall survival prediction, radiomics features were selected via a random forest–based algorithm and Cox regression analysis, respectively. Relevant features were used to build multivariate Cox regression models and calculate the radiomics score. Human papillomavirus status and overall survival prediction were assessed via the area under the curve and concordance index, respectively. The models were validated in the test and The Cancer Imaging Archive cohorts (n = 78).RESULTS: For prediction of human papillomavirus status, radiomics features yielded areas under the curve of 0.865, 0.747, and 0.834 in the training, test, and validation sets, respectively. In the univariate Cox regression, the human papillomavirus status (positive: hazard ratio, 0.257; 95% CI, 0.09–0.7; P = .008), T-stage (>=III: hazard ratio, 3.66; 95% CI, 1.34–9.99; P = .011), and radiomics score (high-risk: hazard ratio, 3.72; 95% CI, 1.21–11.46; P = .022) were associated with overall survival. The addition of the radiomics score to the clinical Cox model increased the concordance index from 0.702 to 0.733 (P = .01). Validation yielded concordance indices of 0.866 and 0.720.CONCLUSIONS: CT-based radiomics may be useful in predicting human papillomavirus status and overall survival in patients with oropharyngeal squamous cell carcinoma.AUCarea under the curveHPVhuman papillomavirusOPSCCoropharyngeal squamous cell carcinomaOSoverall survivalrad-scoresradiomics scoresTCIAThe Cancer Imaging Archive